Pelatihan Internet of Things (IoT) guna Meningkatkan Kompetensi Siswa SMKN 1 Pringgabaya - Mandala Putra, Hadian; Nuzuluddin, M.; Akbar, Taufik; Ahmadi, Ahwan (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
Increasing competence is very necessary for SMK students to improve their insight and knowledge in a world with very rapid technological developments. Increasing competence certainly supports students in preparing for the world of work and becomes a provision for higher education with appropriate fields of competence. In this case, the Computer Engineering Study Program of Hamzanwadi University takes a role in community service by providing Internet of Things (IoT) training to support the competence of vocational students. The competency improvement training was given to students of SMKN 1 Pringggabaya, East Lombok, with a total of 40 students. The training provided was in the form of IoT implementation for intelligent homes, in the form of Light Emitting Diode (LED) control as a substitute for house lights connected to the ESP32 microcontroller and several electronic components, while monitoring and controlling was carried out using a smartphone connected to the internet. In its implementation, the method used is to provide an understanding of the knowledge of IoT, and the application of IoT in several fields, followed by trying to practice the implementation of a smart home which is also implemented and tested directly by students. The results obtained from the training show students' interest in IoT implementation and enthusiasm for understanding IoT implementation now.